168k views
5 votes
Solve for e:
-13 + 7e = -3e - 33

2 Answers

2 votes

Answer:

e = -2

Explanation:

= 7e + 3e = -33 + 13

= 10e = -20

= e = -2

User James Daniels
by
5.0k points
1 vote

Answer:

e = -2

Explanation:

-13+7e=-3e-33

We move all terms to the left:

-13+7e-(-3e-33)=0

We get rid of parentheses

7e+3e+33-13=0

We add all the numbers together, and all the variables

10e+20=0

We move all terms containing e to the left, all other terms to the right

10e=-20

e=-20/10

User Sharena
by
4.9k points